The heel influence on ship manoeuvrability: Single and twin-screw surface vessels. (15th December 2022) - Piaggio, B.; Franceschi, A.; Villa, D.; Ferrari, V.; Tonelli, R.; Viviani, M.
Abstract: Low transverse metacentric height and high speed are peculiar destabilising factors in ship manoeuvrability according to the attainable large heeling angles. The phenomenon indeed occurs in the case of vessels characterised by loading conditions with low transverse stability — e.g. high centre of mass of container vessels and RoRos. Starting from Kijima's single-screw container vessel evidence, an extension of the study to twin-screw ferry vessels is undertaken, with the scope of quantifying its effect in terms of turning and zig-zag IMO margins at an early design stage. Given the relevant impact, an enlarged captive model testing campaign executed on a sample of reference vessels was analysed to further characterise and extend the concepts to a broader class of modern single and twin-screw vessels, thus motivating the study. As a further result, this analysis allowed to underline the need of a review of the IMO intact stability code when dealing with heeling angle during a turn. Highlights: A state-of-the-art model of the heel effect on manoeuvring is laid. The heel effect destabilises the manoeuvring with severe implications on IMO standards. A generalised formulation of the heel effect is proposed. Experimental manoeuvring results are presented and discussed. A series of vessels is studied to prove the generalised hydrodynamic tendencies.